Images : - Seddon, Tony (RotoVision, 2007)
For many graphic designers, problems with sourcing and storing images are a major cause of frustration, stress, expense and delay. Images: A Creative Digital Workflow for Graphic Designers is a consolidated resource manual, arming designers with a thorough understanding of creative asset management procedures to ensure smooth-running projects and success in producing all forms of illustrated design work. Combining the latest technical expertise with sound professional advice, from the most basic, practical issues to in-depth, technical considerations, the book offers hands-on advice for avoiding -- and solving -- problems.